Decreasing matrix modulus of PEG hydrogels induces a vascular phenotype in human cord blood stem cells. (September 2015) - Mahadevaiah, Shruthi; Robinson, Karyn G.; Kharkar, Prathamesh M.; Kiick, Kristi L.; Akins, Robert E.
Abstract: Adult and congenital cardiovascular diseases are significant health problems that are often managed using surgery. Bypass grafting is a principal therapy, but grafts fail at high rates due to hyperplasia, fibrosis, and atherosclerosis. Biocompatible, cellularized materials that attenuate these complications and encourage healthy microvascularization could reduce graft failure, but an improved understanding of biomaterial effects on human stem cells is needed to reach clinical utility. Our group investigates stem-cell-loaded biomaterials for placement along the adventitia of at-risk vessels and grafts. Here, the effects of substrate modulus on human CD34+ stem cells from umbilical cord blood were evaluated. Cells were isolated by immunomagnetic separation and encapsulated in 3, 4, and 6 weight% PEG hydrogels containing 0.032% gelatin and 0.0044% fibronectin. Gels reached moduli of 0.34, 4.5, and 9.1 kPa. Cell viability approached 100%. Cell morphologies appeared similar across gels, but proliferation was significantly lower in 6 wt% gels. Expression profiling using stem cell signaling arrays indicated enhanced self-renewal and differentiation into vascular endothelium among cells in the lower weight percent gels. Thus, modulus was associated with cell proliferation and function. Gels with moduli in the low kilopascal range may be useful in stimulating cell engraftment and microvascularization of graft adventitia.